Familial non-syndromal thoracic aortic aneurysms and dissections — Incidence and family screening outcomes. (1st October 2016) - Robertson, Elizabeth N.; van der Linde, Denise; Sherrah, Andrew G.; Vallely, Michael P.; Wilson, Michael; Bannon, Paul G.; Jeremy, Richmond W.
Abstract: Background: Non-syndromal thoracic aortic aneurysm and dissection (ns-TAAD) is a genetic aortopathy, with uncertain incidence. This study documented the incidence of ns-TAAD and outcomes of family screening over 15 years. Methods: Consecutive series of 2385 patients with aortic disease in prospective registry (2000 to 2014), including 675 undergoing surgery. Diagnosis of ns-TAAD included family history, aortic imaging, tissue pathology and mutation testing. Screening was offered to relatives of ns-TAAD probands, with follow-up for affected individuals. Results: There were 270 ns-TAAD probands (74% males), including 116 (43%) presenting with aortic dissection. Among surgical cases, a diagnosis of ns-TAAD was established for 116 (17%). Age of probands was 50.4 ± 14.1 years, with aortic diameter of 51 ± 12 mm. Screening of 581 at-risk relatives identified 216 new ns-TAAD cases (detection rate = 37%). Among 71 probands with known family history, screening identified 130 new affected relatives and among 53 probands with no family history, screening identified 86 new affected relatives. Mean age of new affected relatives at diagnosis was 44 ± 18 years, with aortic diameter of 42 ± 7 mm, including 42 with diameter > 50 mm. Ten-year mortality was similar for probands without dissection (7.7 ± 3.1%) and new affected relatives (11.4 ± 4.0%) but greater for probands surviving initial dissection (27.6 ± 7.8%, p = 0.003). Conclusions: Up to 1 in 6 patients undergoing aortic surgery have features of ns-TAAD, frequently presenting as aortic dissection but at later age than other genetic aortopathies. Family screening identifies affected relatives in up to half of ns-TAAD probands, many of whom already have significant aortic dilatation.